2016
DOI: 10.21474/ijar01/2348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Ofhalal Tallow and Haram Lardcombinations on Growth Performance, Immunity, Cecalmicrobiology and Noxious Gas Emissionsin Boilers.

Abstract: The study was conducted with an aim to study the animal fat as single (halal tallow) and combined state (halal tallow and haram lard combination) on growth performance, relative organ weight, cecal microbiology and noxious gas concentration in broilers on the aspect of halal ethical issue. Following completely randomized design, a total of 96 day old Ross broiler chicks were allocated into two treatments (TLO: Basal diet with tallow; TPL: Basal diet with tallow+lard), where there was six replications with eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In it, 180 unsexed one-day-old broiler chicks were usedRoss308 average weight is 40 g, the chicks were raised on four Batteries, and each battery has three floors, and each floor contains 2 cages away(1 x 1 m), inside a 6 x 12 m hall. Chicks were randomly distributed into six experimental treatments, with 30 chicks for each treatment, and three replications for each treatment (10).chicks/Duplicate), The chicks were fed on readymade rations (fodder pellets). (Pellet, which was prepared from local markets, produced by the Oasis Factory) and included three relationships: The first bush Starter (Crude Protein 22-23%)And the3010Kk represented energy It was used from the age of 1-14 days and the second diet (crude protein percentage 21-22%)And the3100Kk represented energy) used From the age of 15-28 days and the third diet (crude protein percentage 18-19%And the315th0Kk represented energy) was used from day 29 until the end of the experiment at the age of 42 days.…”
Section: Materials and Methods: Experience Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In it, 180 unsexed one-day-old broiler chicks were usedRoss308 average weight is 40 g, the chicks were raised on four Batteries, and each battery has three floors, and each floor contains 2 cages away(1 x 1 m), inside a 6 x 12 m hall. Chicks were randomly distributed into six experimental treatments, with 30 chicks for each treatment, and three replications for each treatment (10).chicks/Duplicate), The chicks were fed on readymade rations (fodder pellets). (Pellet, which was prepared from local markets, produced by the Oasis Factory) and included three relationships: The first bush Starter (Crude Protein 22-23%)And the3010Kk represented energy It was used from the age of 1-14 days and the second diet (crude protein percentage 21-22%)And the3100Kk represented energy) used From the age of 15-28 days and the third diet (crude protein percentage 18-19%And the315th0Kk represented energy) was used from day 29 until the end of the experiment at the age of 42 days.…”
Section: Materials and Methods: Experience Designmentioning
confidence: 99%
“…[9] that pomegranate peels contain active compounds such as polyphenols (binoclagen and ellagic acid) that give them antioxidant properties and thus maintain vitality and activity of the cell, and this, in turn, is reflected in the vitality and activity of the body. [10]concluded that the high levels of fermented pomegranate peel 2% in broiler diets, led to a significant improvement in both body weight, weight gain, and feed conversion factor compared to levels of 0.5 and 1%. Explained [11]The addition of aqueous extract of pomegranate peels in three concentrations of 50, 75, and 100 ml / per liter for drinking broilers.…”
Section: Introductionmentioning
confidence: 97%
“…Compared to other animals (dairy and swine), poultry occupies the leading position in the quantities of H2S (0.33 ppm) emitted in houses [73]. In addition, the source of fat added to chicken diets plays a role in the quantities emitted from this gas [74]. In the direct form of the effect, at high concentrations, the bird's respiratory system is affected immediately, Klentz and Fedde [75] indicated that exposing the birds to a concentration of 4000 ppm caused an increase in the respiratory frequency and finally the death of the bird within a short period (15 minutes).…”
Section: Hydrogen Sulphidementioning
confidence: 99%